Patterns of spatial co-location of the aerospace industry in Mexico - Villarreal González, Amado; Flores Sánchez, Saidi Magaly; Flores Segovia, Miguel Alejandro (Estudios Económicos de El Colegio de México, 2016)
Mexico’s aerospace industry (IA) is considered strategic due to the possibilities offered to national business to be inserted into supply chain; by its productive characteristics involves the development of suppliers by externalities, which requires business co-location. This document applies the Co-location Quotient (CLQ) statistic in five Mexican entities in order to detect spatial co-location patterns in clusters related to the IA. The results indicate its spatial attraction to aerospace business, as well as electronics, machinery and equipment. Additionally, it can be identified differences in regards colocation patters with respect to the productive capacities by entity; this suggests inputs for the design of industrial policy.